Stone Barrington : Hot Mahogany - Book 15 - Woods, Stuart (New York, N.Y. : Signet, 2009)
CIA boss Lance Cabot hires Stone Barrington to watch over his brother Barton, a former army intelligence officer suffering from amnesia. As Stone discovers, Barton is a spy with a rather unusual hobby: building and restoring antique furniture. Barton is also a man with a past that is linked to the jungles of Vietnam more than thirty years earlier. Stone soon finds out that Barton, and some shady characters of his acquaintance, may be hiding a lot more than just a few forged antiques.
"A Stone Barrington novel."--Cover, p. [1].
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- Fiction; Detective and mystery fiction